Promising therapeutic potential of pterostilbene and its mechanistic insight based on preclinical evidence - Kosuru R.; Rai U.; Prakash S.; Singh A.; Singh S. (My University, 2025)
Pterostilbene (PS) is a well-recognized antioxidant that primarily exists in blueberries, grapevines and heartwood of red sandalwood. Interest in this compound has been renewed in recent years, and studies have found that PS possesses an array of pharmacological properties, including chemopreventive, antiinflammatory, antidiabetic, antidyslipidemic, antiatherosclerotic and neuroprotective effects. However, the greater in vivo bioavailability of PS, as compared to resveratrol, is an added advantage for its efficacy. This review provides a summary regarding the sources, pharmacokinetic aspects and pharmacodynamics of PS, with a focus on the molecular mechanisms underlying its protective effects against cancer, brain injuries and heart disease. Studies regarding the safety profile of PS have also been included. Based on the presently available evidence, we conclude that PS represents an active phytonutrient and a potential drug with pleiotropic health applications. © 2016 Elsevier B.V.